Resolution Improvement in Fabry-Perot Displacement Sensor Based on Fringe Counting Method - Nur Izzati Ismail; Nor Hafizah Ngajikin; Nor Fadzlina Mohd Zaman; Maisarah Awang; Asrul Izam Azmi; Nik Noordini Nik Abd. Malik; Norazan Mohd Kassim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
This paper presents an improved Fringe Counting Method (FCM) technique in order to enhance the displacement resolution of a Fabry-Perot Displacement Sensor (FPDS). A simulation model of a FPDS based on the improved FCM has been developed and simulated for nanometer displacement range by using MATLAB mathematical software. Unlike conventional FCM that analyzed the number of fringes produced over one time period, the improved FCM analyzed the number of fringes for one largest Free Spectral Range (FSR). In this work, the initial length of Fabry-Perot Interferometer (FPI) cavity has been set at 75 μm due to limitation of the machining precision equipment. For the displacement analysis, the improved FCM technique is used as an algorithm. The research results prove that this FPDS could detect displacement at 10nm resolution over a working range of 40 nm. It showed that the improved FCM technique managed to enhance the capability of the conventional FCM in detecting nanometer displacement.